The Roles of Job Autonomy and Self-Efficacy to Improve Academics’ Work-life Balance - Badri, Siti Khadijah Zainal; Panatik, Siti Aisyah (Asian Academy of Management Journal, 2020)
Discussion on workers’ work-life balance has been ongoing since the 1980s. However, less is known about work-life balance amongst university academics especially on the role of job autonomy and self-efficacy in influencing it. The current paper investigates the influence of job autonomy towards academics’ work-life balance. Also, it examines the role of self-efficacy as a moderator in between this relationship. This study employed a quantitative method using the cross-sectional design using data on 307 responses to test these propositions. Using AMOS 23 and SPSS23, we established evidences on the positive influence of job autonomy towards academics’ work-life balance. That is, high job autonomy linked to higher work-to-family enrichment and lesser work-to-family conflict occurrences. Besides, work-to-family enrichment was found higher when self-efficacy level was high, confirming the moderating role of self-efficacy. This study contributes to a greater understanding on the influence of both job autonomy and self-efficacy towards academics’ work-life balance in terms of enrichment and conflict occurrences. It also affirms the constructive effects of self-efficacy to enhance the relationship between job autonomy and work-to-family enrichment. Findings from this study may be used to assist various human resource practitioners, researchers, and higher education institutions to build relevant policies to further support sustainable work-life balance practices within educational institutions.